Asarone inhibits adipogenesis and stimulates lipolysis in 3T3-L1 adipocytes. - Lee, S. H.; Kim, K-Y.; Ryu, S. Y.; Yoon, Y.; Hahm, D-H.; Kang, S. A.; Cho, S. H.; Lim, J-S.; Moon, E-Y.; Yoon, S. R.; Lee, H. G.; Yoon, D. Y.; et al. (Cellular and Molecular Biology, 2010)
Asarone is a molecule found in certain plants such as Acorus calamus, the root of which is used in traditional medicine to treat diabetes. We determined the molecular mechanism underlying the anti-diabetic activity of asarone. Treatment of asarone significantly inhibited the differentiation of 3T3-L1 preadipocytes through suppression of expression of the transcription factors, CCAAT/enhancer binding protein-Î± and peroxisome proliferator activated receptor-Î³, which activate adipogenesis. Intracellular triglyceride levels were reduced by asarone in a dose-dependent manner and asarone treatment stimulated the phosphorylation of hormone-sensitive lipase. Together, the present findings indicate that asarone inhibits adipogenesis by down-regulation of PPARÎ³ and C/EBPÎ± and reduces lipid accumulation by stimulation of lipolysis through an increase in hormone-sensitive lipase activity.